Use of Baricitinib in Patients With Moderate to Severe Coronavirus Disease 2019. (29th June 2020) - Titanji, Boghuma K; Farley, Monica M; Mehta, Ashish; Connor-Schuler, Randi; Moanna, Abeer; Cribbs, Sushma K; O'Shea, Jesse; DeSilva, Kathryn; Chan, Bonnie; Edwards, Alex; Gavegnano, Christina; Schinazi, Raymond F; et al.
Abstract: Hyperinflammation is associated with increased mortality in coronavirus disease 2019 (COVID-19). In this retrospective, uncontrolled patient cohort with moderate -severe COVID-19, treatment with baricitinib plus hydroxychloroquine was associated with recovery in 11 of 15 patients. Baricitinib for the treatment of COVID-19 should be further investigated in randomized, controlled clinical trials.